Assessing endotoxins in equine-derived snake antivenoms: Comparison of the USP pyrogen test and the Limulus Amoebocyte Lysate assay (LAL). (October 2015) - Solano, Gabriela; Gómez, Aarón; León, Guillermo
Abstract: Snake antivenoms are parenterally administered; therefore, endotoxin content must be strictly controlled. Following international indications to calculate endotoxin limits, it was determined that antivenom doses between 20 mL and 120 mL should not exceed 17.5 Endotoxin Units per milliliter (EU/mL) and 2.9 EU/mL, respectively. The rabbit pyrogen test (RPT) has been used to evaluate endotoxin contamination in antivenoms, but some laboratories have recently implemented the LAL assay. We compared the capability of both tests to evaluate endotoxin contamination in antivenoms, and we found that both methods can detect all endotoxin concentrations in the range of the antivenom specifications. The acceptance criteria of RPT and LAL must be harmonized by calculating the endotoxin limit as the quotient of the threshold pyrogenic dose and the therapeutic dose and the dose administered to rabbits as the quotient of the threshold pyrogenic dose and the endotoxin limit. Since endotoxins from Gram-negative bacteria exert different pyrogenicity, if contamination occurred, antivenom batches that induce pyrogenic reactions may be found in spite of passing LAL specifications. Although LAL assay can be used to assess endotoxin content throughout the antivenom manufacturing process, we recommend that the release of final products be based on the results of both methods. Highlights: The acceptable content of endotoxin in antivenoms varies from one product to another. Endotoxin content for antivenoms is detected by the USP pyrogen and the LAL tests. Different pyrogenicity of endotoxins from diverse Gram-negative bacteria was tested. LAL can be used to detect endotoxin throughout the antivenom manufacturing process. The release of final products should be also based on the USP pyrogen test results.